2021
DOI: 10.37506/ijfmt.v15i1.13718
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soft Cheese in Reducing of Lipid Profile and Liver Enzymes for Rats with Fat Disorder

Abstract: Aim: This study was designed to determine the impact of soft cheese upon total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), very low-density lipoprotein cholesterol (VLDL) and the efficacy of liver enzymes AST, ALT, and ALP in hyperlipidemia experimental Sprague-Dawley rats. Materials & Methodology: Rats were divided into five groups (six rats each), healthy control group, hyperlipidemia control group, and three hyperlipidemia grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…It also agreed with the study [23] which found that oral administration of zinc nanoparticles had a positive effect on lipid-painter improvement. It also agreed with the study of [24] which demonstrated the possibility of soft cheese in lowering the fat levels of feeding rats on high fat leeches and its ability to process them. There has also been a positive change in fat levels in the nutritious rat aggregates with high calorie tenderness with nanoscale zinc oxide dosage and thus a decrease in their levels which has been positively reflected in animal health.…”
Section: The Effect Of Oral Administration Of Different Transactions ...supporting
confidence: 90%
See 1 more Smart Citation
“…It also agreed with the study [23] which found that oral administration of zinc nanoparticles had a positive effect on lipid-painter improvement. It also agreed with the study of [24] which demonstrated the possibility of soft cheese in lowering the fat levels of feeding rats on high fat leeches and its ability to process them. There has also been a positive change in fat levels in the nutritious rat aggregates with high calorie tenderness with nanoscale zinc oxide dosage and thus a decrease in their levels which has been positively reflected in animal health.…”
Section: The Effect Of Oral Administration Of Different Transactions ...supporting
confidence: 90%
“…As between [33] nutrition with a high calorie stick caused a rise in liver-saturated fatty acids and therefore elevated liver enzymes as a result of liver damage. These findings also coincided with the findings of [34]. In their study, the nutrition of soft cheese gave a positive role in the level of liver enzymes compared to overlipid rats and was not treated.…”
Section: Effect Of Oral Administration Of Different Transactions In L...supporting
confidence: 83%